Sandra González - Surface Modifications of Cop-Based Microfluidic Devices for Improved Inmobilization of Hydrogel Proteins: Long Term 3D culture with Contrative Cell Types and Ischemia Model - González, Sandra (Jornada de Jóvenes Investigadores del I3A, 2022)
Sandra González - Surface Modifications of Cop-Based Microfluidic Devices for Improved Inmobilization of Hydrogel Proteins: Long Term 3D culture with Contrative Cell Types and Ischemia Model